PERBANDINGAN PERFORMANSI ANTARA MONGODB DAN MARIADB - Dibyo Sudarsono; Mutiara Dwi Anggraini; Christina Andriyani; Mukhadimah; Agun Nurul Widiyanto; Fahmi Ilmawan; Ema Utami (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
Along with the use of information technology in almost all sectors of life, making databases has a very important role in being able to store and process large amounts of data effectively, and high performance is required when processing the database. The Nosql database is widely used in managing very large amounts of data besides that it is also an open source database, but so far many still use the mysql database which is an open source DBMS and has many communities. This paper will compare the performance between a relational database that stores structured data (Sql) and a database with a dynamic and unstructured schema (Nosql). Specifically the database being compared between MariaDB and MongoDB. An experiment will be carried out by performing a query insert, update, delete on the two databases, with the number of records of 500, 1000, 5000, 7500 and 10000, besides that, it is also tested for a select query without criteria, with 1 criterion and 2 criteria. And from the experiments conducted it can be concluded that for insert, update and delete queries on a single NoSQL table has a much better response time. Whereas the select query without NoSQL criteria also has a better response time, but to display all data with criteria, especially the two database criteria, the SQL version has a better response time than NoSQL.